Marginalized mothers, mothering from the margins - Taylor, Tiffany, 1972-; Bloch, Katrina (Advances in gender research ;, 2018)
This volume focuses on the ways in which mothers aremarginalized based on intersecting identities, such as immigration status, race, class, disability, sexuality, and how these women mother from the margins. Divided into three sections, this collection brings forth the voices andexperiences of mothers and highlights the institutions and laws that marginalize them. In the first section, mothers face barriers such as institutional constraints that block them from needed resources and the ability to mother as they see fit. In section two, contributors examine theborders of marginalized mothering - boundaries reflected through citizenship, walls, geography, dealings with intimate partners and welfare offices, or prison bars. Readings in this section highlight mothers' efforts to transcend, resist, or even just survive experiences with borders.The final section centers on mothers that explicitly adopt mothering strategies of resistance or explicitly use their status as mothers in their activism. Topics range from mothers who engage in milk sharing to mothers of color whom organize against police brutality.Throughout the volume, contributors demonstrate the striking resilience of these mothers, and their resistance in challenging the ideologies and institutions that marginalize them.